2015
DOI: 10.1590/0103-8478cr20140098
|View full text |Cite
|
Sign up to set email alerts
|

Compostos fenólicos e capacidade antioxidante em frutos de tomateiros mutantes fotomorfogenéticos

Abstract: RESUMO Compostos fenólicos e capacidade antioxidante são mecanismos de defesa das plantas aos danos do estresse oxidativo. Os compostos fenólicos são sintetizados pela via dos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…We conclude that, considering the higher PSII operating efficiency and ETR during the water withholding treatment, tomato photomorphogenic mutants au and hp1 present higher tolerance to water stress when compared to the wild-type MT. Some evidence shows that light, operating via the phytochrome, is connected to the regulation of antioxidant enzyme activity (Drumm and Schopfer 1974;Zhong et al 1994Zhong et al , 1997Mullineaux et al 2000) and to the biosynthesis of antioxidant compounds, including carotenoids and phenolic compounds (Pizarro and Stange 2009;Toledo-Ortiz et al 2010;Dias et al 2015). Therefore, the tolerance of mutants to the effects of water withholding may be explained by the higher activity of antioxidant enzymes, such as CAT and APX, in au and by a higher concentration of antioxidant compounds, such as carotenoids, in hp1.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that, considering the higher PSII operating efficiency and ETR during the water withholding treatment, tomato photomorphogenic mutants au and hp1 present higher tolerance to water stress when compared to the wild-type MT. Some evidence shows that light, operating via the phytochrome, is connected to the regulation of antioxidant enzyme activity (Drumm and Schopfer 1974;Zhong et al 1994Zhong et al , 1997Mullineaux et al 2000) and to the biosynthesis of antioxidant compounds, including carotenoids and phenolic compounds (Pizarro and Stange 2009;Toledo-Ortiz et al 2010;Dias et al 2015). Therefore, the tolerance of mutants to the effects of water withholding may be explained by the higher activity of antioxidant enzymes, such as CAT and APX, in au and by a higher concentration of antioxidant compounds, such as carotenoids, in hp1.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of tannins (TAN) in wine was defined by maximum air temperatures and higher thermal amplitudes, in contrast, lower effects of incident solar radiation and rainfall. Research has shown that the phenolic compounds of the wine are determined by the enzymatic activity of the phenylalanine ammonia-lyase (PAL), which is dependent on the quality and light intensity, as well as on the incident radiation balance (Dias et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Para fins de comparação com um fruto da mesma família botânica, Tamer et al (2010) encontraram 476,6 mg/100 g de polpa de compostos fenólicos em Cucurbita moschata L, teores inferiores aos encontrados em cruá vermelho. Os compostos fenólicos são grupos variados de produtos do metabolismo secundário dos vegetais e apresentam alta capacidade antioxidante (Dias et al, 2015). Segundo Kuskoski et al (2006) e Melo et al (2008), os compostos fenólicos são os principais responsáveis pela capacidade antioxidante em frutos, sendo responsáveis por mais de 90% da capacidade antioxidante total de frutos.…”
Section: Compostos Fenólicos Antocianinas E Capacidade Antioxidanteunclassified